The Effect of Content-Related and Unrelated Humor on Academic Engagement in Fourth-Grade Male Elementary Students - Tavakolian , Mehrzad; Asadzadeh , Hassan; Hosseini-Almadani, Seyed Ali; Jalili Shishvan, Ali (KMAN Counseling & Psychology Nexus, 2025)
This study aimed to investigate the effect of content-related and content-unrelated humor on academic engagement among fourth-grade male students in Tehran. A quasi-experimental research design with pretest-posttest and control group structure was used. The statistical population included all fourth-grade male students in non-profit schools in District 5 of Tehran during the 2023–2024 academic year. Through multi-stage cluster sampling, three schools and three fourth-grade male classes were selected, with two classes assigned to the intervention groups (content-related and unrelated humor) and one class to the control group. A total of 88 students completed the study (29 in each intervention group and 30 in the control group). The academic engagement questionnaire by Wang et al. (2011), validated for Iranian samples, was used to assess outcomes. The intervention consisted of eight 45-minute sessions, in which science content was taught using either content-related humor or unrelated humor. Data were analyzed using ANCOVA and post hoc LSD tests in SPSS-23. The ANCOVA results indicated a significant effect of the intervention on academic engagement (F(2, 86) = 16.688, p < 0.001, η² = 0.14), showing that 14% of the variance in posttest scores was due to group membership. Post hoc comparisons revealed that the content-related humor group had significantly higher academic engagement than both the content-unrelated humor group (mean difference = 1.543, p < 0.001) and the control group (mean difference = 1.335, p < 0.001). However, no significant difference was found between the content-unrelated humor group and the control group (p = 0.348). The results demonstrate that humor strategies aligned with academic content significantly enhance student engagement, while unrelated humor does not yield a meaningful effect. Content-related humor should be prioritized as a pedagogical tool for fostering academic engagement in elementary education.